Blue carbon in Brazilian mangroves: from soil geochemistry to soil quality assessment and public management - Jimenez, Laís Coutinho Zayas (2024)
Mangroves play a pivotal role in providing a diverse array of ecosystem services, making invaluable contributions to the environment and society. While their capacity to sequester and store carbon, particularly in soils, has garnered significant attention, a substantial proportion of mangrove vegetation worldwide has already undergone degradation. Aligned with the United Nations Decade on Ecosystem Restoration and with de Ocean Decade of United Nations, the primary objective of this doctoral thesis is to comprehend the intricate geochemical processes involved in restoring carbon stocks in mangrove soils, with a particular emphasis on the critical role of the mineral fraction, notably iron, in carbon accumulation during early and long-term ecosystem development. This understanding is elucidated in the first and second chapters of the thesis. The first chapter explores the significance of organomineral associations during the early stages of mangrove development, elucidating their pivotal role in the protection and accumulation of organic matter. Additionally, the second chapter delves deeper into the associations between iron and organic matter in soils undergoing restoration, highlighting the prominence of oxidized forms in these processes. Furthermore, the thesis investigates the dynamics of mangrove development and its impact on enhancing soil quality. In the third chapter, an evaluation of soil quality changes along a long-term chronosequence of mangrove development is conducted to mangrove soils. Recognizing the significance of soil quality indexes in scientific communication, the study extends its focus to comprehend the extent of interactions among scientific, public, and civil perspectives on this ecosystem. The fourth and final chapter examines the multifaceted perspectives on mangroves, encompassing academic research, and public managerial strategies, and the involvement of civil society ins mangroves located in protected areas from São Paulo. By comprehensively examining these diverse approaches, the study emphasizes the necessity of establishing effective channels of communication and fostering collaborative efforts among various stakeholders. Such coordination is indispensable for ensuring the successful conservation and restoration of these invaluable ecosystems, taking into account the diverse perspectives and interests involved.